Applying the Theory of Planned Behaviour to Tourism-Related Waste Behaviour in Marine Protected Areas: The Aliwal Shoal Case Study - HARPER, Carrigan; ROOS, Claudine; RETIEF, Francois Pieter; ALBERTS, Reece Cronje; CILLIERS, Dirk Petrus (Journal of Environmental Management and Tourism; Vol 13 No 3 (2022): JEMT, Volume XIII, Issue 3(59), Summer 2022, 2022)
This paper aims to better understand tourism-related waste behaviour within marine protected areas (MPAs) by applying the Theory of Planned Behaviour (TPB) to a specific South African case study. Observed- and self-reported elements of waste separation behaviour were determined for four diving charters and five accommodation facilities within the Aliwal Shoal MPA. Observations and waste characterisation were performed to understand actual behaviour, while survey questionnaires based on the TPB were administered to determine self-reported behaviour. Interviews were conducted to explore challenges and opportunities for waste separation at source. The results found a significant percentage of recyclable waste (>70%) within the disposable waste stream, and no waste separation infrastructure at any of the facilities investigated. Survey responses indicated a positive attitude towards waste separation, with a social drive towards participating. Respondents also indicated that they generally participated in waste separation at source, a claim not supported by the observation data. The identified challenges for waste separation at source included a lack of separation infrastructure and collection services, inconvenience, time constraints, and unwillingness of customers to participate. Accordingly, the main opportunities towards waste separation included the provision of waste separation resources and reliable municipal services, and strategies towards improved waste-related awareness and behaviour.